Overly broad-spectrum antibiotic treatment of wild-type Pseudomonas aeruginosa infections in relation to the EUCAST new definition of susceptibility testing categories, a retrospective multicentre cohort study. Issue 5 (17th October 2022) - Ourghanlian, Clément; Fihman, Vincent; Morel, Antoine; Lafont, Charlotte; Galy, Adrien; Calimouttoupoulle, Eimma; Woerther, Paul-Louis; Lepeule, Raphaël
Abstract: Objectives: EUCAST changed the definition of the 'intermediate' (I) category in 2019, now defined as 'susceptible, increased exposure'. This new definition could lead to an increased prescription of antibiotics still reported as 'S', compared with those now reported as 'I'. The objective of this study was to evaluate the influence of this definition on the use of overly broad-spectrum antibiotics for the treatment of infections caused by WT Pseudomonas aeruginosa . Methods: A retrospective observational multicentre study was conducted, involving five hospitals. Two 15 month study periods were defined, before and after the implementation of the new definition. All patients with an infection caused by WT P. aeruginosa treated by β-lactams were included. The main endpoint was the proportion of patients treated by an overly broad-spectrum antibiotic treatment by meropenem or ceftolozane/tazobactam. Results: Two hundred and ninety-one patients were included. No difference between groups was found, in terms of infection, microbiology or demographic characteristics. Two overly broad-spectrum antibiotic treatments by meropenem or ceftolozane/tazobactam were observed in Period 1 (1.2%), versus 13 in Period 2 (10.8%; P  < 0.001). No overly broad-spectrum treatment was observed when the antimicrobial stewardship team had given advice. Conclusions: This new definition can cause a negative impact on the use of overly broad-spectrum antibiotic treatment due to misunderstanding by clinicians. Its successful implementation requires adaptation of software for reporting antibiotic susceptibility, a sustained strong information campaign by microbiologists and support by an antimicrobial stewardship team.